2010
DOI: 10.1094/php-2010-0827-01-br
|View full text |Cite
|
Sign up to set email alerts
|

Occurrences of Soybean Viruses, Fungal Diseases, and Pests in Illinois Soybean Rust Sentinel Plots

Abstract: After soybean rust was confirmed in soybean in the USA, sentinel plots were established in 26 states to monitor its spread. Funding for establishing, sampling, and monitoring the plots came from the USDA, national, regional, and state soybean commodity boards, and state departments of agriculture, extension services, and universities. The presence of sentinel plots for soybean rust monitoring provided the potential for reducing the time and expense of extensive statewide travel for collection of soybean leaf s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…In 2008 and 2009, soybean leaf samples were collected without regard to disease symptoms at growth stages R5 to R7 (Fehr et al, 1971) from commercial soybean fields in 36 and 9 counties respectively, in Illinois, USA (Hobbs et al, 2010). Leaf samples (over 3,000 in total) were combined into groups of about 90 leaves, total RNA was extracted using the Qiagen (Valencia, CA) RNeasy Plant Mini Kit for 150 mg of leaf tissue from each pool.…”
Section: Plant Materials and Total Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…In 2008 and 2009, soybean leaf samples were collected without regard to disease symptoms at growth stages R5 to R7 (Fehr et al, 1971) from commercial soybean fields in 36 and 9 counties respectively, in Illinois, USA (Hobbs et al, 2010). Leaf samples (over 3,000 in total) were combined into groups of about 90 leaves, total RNA was extracted using the Qiagen (Valencia, CA) RNeasy Plant Mini Kit for 150 mg of leaf tissue from each pool.…”
Section: Plant Materials and Total Rnamentioning
confidence: 99%
“…Leaf samples (over 3,000 in total) were combined into groups of about 90 leaves, total RNA was extracted using the Qiagen (Valencia, CA) RNeasy Plant Mini Kit for 150 mg of leaf tissue from each pool. RNA samples were treated with DNase I and evaluated for integrity by agarose gel electrophoresis (Hobbs et al, 2010).…”
Section: Plant Materials and Total Rnamentioning
confidence: 99%
“…Although SbDV has the ability to be a devastating disease and an aphid vector that colonizes soybean is now present in the United States, we have not seen evidence of a marked increase in SbDV incidence in soybean production fields (14,38).…”
Section: Discussionmentioning
confidence: 59%
“…In 1993, the aforementioned diseases were reported as the most frequently occurring foliar diseases in an evaluation period of 13 yr from disease‐monitoring plots in Illinois (Eathington et al, 1993). In a more recent report (Hobbs et al, 2010), the most common foliar diseases in Illinois were brown spot, reported in 100 and 96% of the survey samples in 2006 and 2007, respectively, followed by Cercospora leaf blight (89%, 2007), downy mildew (96 and 67% in 2006 and 2007, respectively), and frog‐eye leaf spot (60 and 78% in 2006 and 2007, respectively). Bacterial pustule was less common and was found in only 4% of the samples in 2007.…”
mentioning
confidence: 97%